Iterative Calibration of VISSIM Simulator Based on Genetic Algorithm - Tettamanti, T.; Csikós, A.; Varga, I.; Eleőd, A. (Acta Technica Jaurinensis, 2015)
In the recent decade, computer simulation has been developed enormously in all engineering fields and has become a basic step of design. Accordingly, simulation plays a fundamental role in road traffic engineering offering a basis for the effective analysis of intelligent traffic control systems. A reliable simulator is able to provide effective analysis of a given traffic network if the applied simulation scenarios properly converge to the real-word situation. This requirement can be achieved based on the mixed use of prior real-world traffic measurements and proper simulation settings.  The latter one, however, is not straightforward. Accordingly, the paper proposes a potential calibration method to create true-to-life VISSIM simulations. VISSIM is one of the most popular microscopic traffic simulator, a well-known software applied in engineering and scientific practice as well. Basically, a calibration technique with genetic algorithm optimization is proposed to reproduce realistic traffic on a network based on floating car speed data.